Video-based health professional education for postpartum psychosis: acceptability and changes in knowledge amongst primary care workers in Thyolo, Malawi - Kalolo, Gloria (Department of Psychiatry and Mental Health, 2024)
INTRODUCTION Postpartum psychosis is a severe mental health condition that affects women soon after they give birth, and is characterised by disturbances in thought pattern, abnormal behaviour and mood disruption. It is life threatening as women presenting with this condition are at a high risk of suicide and infanticide. Good outcomes such as reduced rate of relapse and better quality of life are expected if pharmacological and psychosocial treatments are initiated early. Stigma by healthcare workers in low- and middle-income countries, including in Malawi, leads to non-identification, late treatment and poor clinical and social outcomes. A video-based educational tool, which includes a narrative of a patient with lived experience of postpartum psychosis was created by the ‘Strengthening the Network for Studying Psychological Resilience in Low-And Middle-income Countries Project (NESP)', for potential use in training professional primary healthcare workers in identification and referral of postpartum psychosis. The aim of this study was to assess change in knowledge of and attitudes towards postpartum psychosis in professional primary healthcare workers in Malawi after watching this video, and to explore their perceptions on the usefulness of the video in their training and daily work. METHOD We conducted a mixed methods study evaluating the effects of a video- based educational tool on knowledge and attitudes of professional primary healthcare workers in Thyolo, Malawi. The Mental Health Knowledge Schedule (MAKS) was used to assess knowledge and Mental Illness Clinicians Attitudes Scale (MICA) was used to assess attitudes before and after exposure to the video. Convenience sampling was used to select 20 out of 28 health centres in Thyolo district. All professional primary healthcare workers at each sampled health centre were invited to participate in the study. A total of 126 participants were recruited and 96 of them completed both pre and post-tests. Then two separate focus group discussions were held with a total of 11 participants attending out of 12 sampled. SPSS version 28 was used to analyse quantitative data: a paired sample t-test was used to assess the unadjusted change in MAKS and MICA scores. A repeated measures ANOVA controlling a priori for age, number of days between pre-post-test and experience with treating PPP was then performed. NVivo 12 was used in the thematic analysis of transcribed qualitative data. RESULTS The results showed significantly higher MAKS (knowledge) scores in the post-test (mean = 23.1, SD = 2.5) compared to the pre-test (mean = 21.9, SD= 2.9) (mean difference = -1.2, t = -3.5, p =